Teknik Pengambilan Keputusan dalam Berorganisasi - Saifudin, Saifudin; Maryanto, Maryanto; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
Decision making is a human cognitive process that results in selecting beliefs or actions among several available alternative options, either rationally or irrationally. In organizations, decision making is a factor that really determines the success of the organization in achieving its stated goals. Decision making is also one of the functions of a leader, therefore every leader must be aware of his strategic position and at the same time strive to be able to make every decision correctly and with quality. Apart from having to master various decision-making techniques, he must also be able to implement them correctly. Because in the end it is the subordinates who will implement every decision taken, the involvement of subordinates in every decision-making process must always be sought. In reality, the color of the decisions taken by a leader will really depend on the style he adopts, but every leader needs to realize that the situation faced is not always the same for everyone. This is where a leader is important in making decisions.